2018
DOI: 10.1186/s12873-018-0192-3
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant polycystic kidney disease and minimal trauma: medical review and case report

Abstract: BackgroundBlunt abdominal trauma in the setting of polycystic kidney disease is still scantly described in the literature and management guidelines of such patients are not well-established.Case presentationThe authors herein present a case of hypovolemic shock secondary to segmental renal artery bleed in a 75-year-old man with polycystic kidney disease after minimal blunt abdominal trauma, who underwent successful selective arterial embolization, and provide a thorough review of similar cases in the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…It has also been shown that increased levels of proteinuria and urinary albumin excretion correlated with higher risk of severe renal disease and progression to ADPKD [12]. Hematuria in ADPKD has been linked with hemorrhage in the cysts or cyst rapture into collecting ducts while, proteinuria occurs due to impaired reabsorption of proteins by cyst-lined tubular epithelia which may not occur at the initial stage of the disease [13]. The multiple urinary tract infections (UTIs) observed in this study could result to more rapid decline in renal function.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that increased levels of proteinuria and urinary albumin excretion correlated with higher risk of severe renal disease and progression to ADPKD [12]. Hematuria in ADPKD has been linked with hemorrhage in the cysts or cyst rapture into collecting ducts while, proteinuria occurs due to impaired reabsorption of proteins by cyst-lined tubular epithelia which may not occur at the initial stage of the disease [13]. The multiple urinary tract infections (UTIs) observed in this study could result to more rapid decline in renal function.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in our study (Table 6 ), proteinuria and hematuria are common observations in ADPKD [ 30 ]. Whereas hematuria in ADPKD mostly occurs either due to hemorrhage into cysts or cyst rapture into collecting ducts, proteinuria occurs due to impaired reabsorption of proteins by cyst-lined tubular epithelia [ 31 ] but is not usually observed in the early stages [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case series of adult patients with ADPKD described several cases of serious bleeding resulting from relatively low-impact events including shock wave lithotripsy, a massage chair, and a fall from standing height. 5 Additionally, hemorrhagic cystic rupture in adult patients has been associated with retroperitoneal hematomas and the development of hypovolemic shock.…”
Section: Discussionmentioning
confidence: 99%